Dependency of the regio- and stereoselectivity of intramolecular, ring-closing glycosylations upon the ring size - Patrick Claude; Christian Lehmann; Thomas Ziegler (Beilstein Journal of Organic Chemistry, 2011)
Phenyl 3,4,6-tri-O-benzyl-2-O-(3-carboxypropionyl)-1-thio-β-D-galactopyranoside (1) was condensed via its pentafluorophenyl ester 2 with 5-aminopentyl (4a), 4-aminobutyl (4b), 3-aminopropyl (4c) and 2-aminoethyl 4,6-O-benzylidene-β-D-glucopyranoside (4d), prepared from the corresponding N-Cbz protected glucosides 3a–d, to give the corresponding 2-[3-(alkylcarbamoyl)propionyl] tethered saccharides 5a–d. Intramolecular, ring closing glycosylation of the saccharides with NIS and TMSOTf afforded the tethered β(1→3) linked disaccharides 6a–c, the α(1→3) linked disaccharides 7a–d and the α(1→2) linked disaccharide 8d in ratios depending upon the ring size formed during glycosylation. No β(1→2) linked disaccharides were formed. Molecular modeling of saccharides 6–8 revealed that a strong aromatic stacking interaction between the aromatic parts of the benzyl and benzylidene protecting groups in the galactosyl and glucosyl moieties was mainly responsible for the observed regioselectivity and anomeric selectivity of the ring-closing glycosylation step.